Roles of endoplasmic reticulum stress in the pathophysiology of polycystic ovary syndrome - Koike, Hiroshi; Harada, Miyuki; Kusamoto, Akari; Xu, Zixin; Tanaka, Tsurugi; Sakaguchi, Nanoka; Kunitomi, Chisato; Azhary, Jerilee M. K.; Takahashi, Nozomi; Urata, Yoko; Osuga, Yutaka (Frontiers in Endocrinology, 2023)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among reproductive-age women, affecting up to 15% of women in this group, and the most common cause of anovulatory infertility. Although its etiology remains unclear, recent research has revealed the critical role of endoplasmic reticulum (ER) stress in the pathophysiology of PCOS. ER stress is defined as a condition in which unfolded or misfolded proteins accumulate in the ER because of an imbalance in the demand for protein folding and the protein-folding capacity of the ER. ER stress results in the activation of several signal transduction cascades, collectively termed the unfolded protein response (UPR), which regulates various cellular activities. In principle, the UPR restores homeostasis and keeps the cell alive. However, if the ER stress cannot be resolved, it induces programmed cell death. ER stress has recently been recognized to play diverse roles in both physiological and pathological conditions of the ovary. In this review, we summarize current knowledge of the roles of ER stress in the pathogenesis of PCOS. ER stress pathways are activated in the ovaries of both a mouse model of PCOS and in humans, and local hyperandrogenism in the follicular microenvironment associated with PCOS is responsible for activating these. The activation of ER stress contributes to the pathophysiology of PCOS through multiple effects in granulosa cells. Finally, we discuss the potential for ER stress to serve as a novel therapeutic target for PCOS.